Analysis of disproportionation process of trifluoroethylene mixtures. (July 2018) - Otsuka, Tetsuo; Ueno, Katsuya; Okamoto, Hidekazu; Ippommatsu, Masamichi; Dobashi, Ritsu
Abstract: Trifluoroethylene (HFO-1123) and its mixtures are useful as the next generation refrigerants because their global warming potential (GWP) are lower than that of those ordinarily used. HFO-1123, however, has the potential to disproportionate explosively as does tetrafluoroethylene. In this report, the explosive disproportionation of mixed gases of HFO-1123 and other gases were investigated by the fusing of Pt wires ignition method at 10 MPa and 488 K which was the upper limit of the conditions in typical refrigerant usage. It was found that there was a roughly linear correlation between the lower limit of HFO-1123 concentration at which disproportionation occurred and the molar heat capacity at a constant volume of mixed gas. This experimental finding strongly suggests that an explosive disproportionation consists of a thermal explosion process. Highlights: The disproportionation concentration of trifluoroethylene mixture was proportional to the mean heat capacity of the mixture. Mixed fluorinated compound reacted to be tetrafluoromethane and hydrofluoride at disproportionation of trifluoroethylene. Tetrafluoropropene and difluoromethane have an effect of suppressing the onset of disproportionation of trifluoroethylene. Tetrafluoropropene and difluoromethane had no roles of radical capping in the disproportionation of trifluoroethylene. The risk of the disproportionation of trifluoroethylene mixture would be evaluated with molar heat capacity of mixture.